Indications, complications and outcomes of elderly patients undergoing retrievable inferior vena cava filter placement. Issue 10 (20th September 2016) - Rottenstreich, Amihai; Kleinstern, Geffen; Bloom, Allan I.; Klimov, Alexander; Kalish, Yosef
Abstract : Aim: The utilization of inferior vena cava filter placement for pulmonary embolism prevention in elderly patients has not been well characterized. The present study aimed to review indications, complications and follow‐up data of elderly patients undergoing inferior vena cava filter placement. Methods: A retrospective review was carried out of consecutive admitted patients who underwent inferior vena cava filter insertion at a large university hospital with a level I trauma center. Results: Overall, 455 retrievable filters were inserted between 2009 and 2014. A total of 133 patients (29.2%) were aged ≥70 years. Elderly patients were less likely to have their filter retrieved compared with non‐elderly patients (5.3% vs 21.4%, P < 0.001). Filter‐related complications occurred in 13% of non‐elderly patients and 14.3% of elderly patients ( P = 0.72), most of them occurring in the first 3 months after filter placement. Survival among elderly patients with no evidence of active malignancy was similar to the non‐elderly patients with a 1‐year survival rate of 76.3% versus 82% in non‐elderly patients ( P = 0.22), and a 2‐year survival rate of 73.1% versus 78.6% in non‐elderly patients ( P = 0.27). Although decreased, survival rates among elderly patients with active cancer were still substantial, with a 1‐year survival rate of 45% and 2‐year survival rate of 40%. Conclusions: Elderly patients had significantly lower rates of filter retrieval with similar complication rate. Survival rates among elderly patients were substantial, and in elderly patients with no active cancer were even comparable with non‐elderly patients. When feasible, filter retrieval should be attempted in all elderly patients in order to prevent filter‐related complications.Geriatr Gerontol Int 2017; 17: 1508–1514.